Silk fibroin for vascular regeneration. Issue 3 (12th June 2015) - Wang, Danyan; Liu, Haifeng; Fan, Yubo
ABSTRACT: Cardiovascular disease is the primary cause of morbidity and mortality in today's world. Due to the lack of healthy autologous vessels, more tissue‐engineered blood vessels are needed to repair or replace the damaged arteries. Biomaterials play an indispensable role in creating a living neovessel with biological responses. Silk fibroin produced by silkworms possesses good cytocompatibility, tailorable biodegradability, suitable mechanical properties, and minimal inflammatory reactions. In addition, regenerated silk fibroin solutions can be processed into various forms of scaffolds such as films, fibers, tubes, and porous sponges. These features make silk fibroin a promising biomaterial for small‐diameter vascular grafts. The present article focuses on the applications of silk fibroin for vascular regeneration. A brief overview of the properties of silk fibroin is provided, following which the current research status and future directions of the main types of silk fibroin scaffolds for vascular regeneration are reviewed and discussed. Microsc. Res. Tech. 80:280–290, 2017. © 2015 Wiley Periodicals, Inc.